Simultaneous identification by multiplex PCR of major Prototheca spp. isolated from bovine and buffalo intramammary infection and bulk tank. (1st December 2014) - Capra, E.; Cremonesi, P.; Cortimiglia, C.; Bignoli, G.; Ricchi, M.; Moroni, P.; Pesce, A.; Luini, M.; Castiglioni, B.
Abstract: Bovine mastitis caused by Prototheca spp. infection is increasing worldwide, therefore becoming more relevant to the dairy industry. Almost all Prototheca isolates from bovine mammary protothecosis came from P. zopfii genotype 2, with a lower prevalence of infection due to P. blaschkeae and rarely to P. wickerhamii . In this study, we report the development of two multiplex PCR assays able to discriminate among the three species responsible for bovine intramammary infection (IMI). Our assay is based on the specific amplification of new DNA target from mitochondria and chloroplasts partial sequences, of different Prototheca isolates. Both methods were set up using reference strains belonging to all Prototheca species and validated by the analysis of 93 isolates from bovine and buffalo IMI and bulk tank milk samples. The investigation involves 70 isolates from North, 13 from Central and 10 from South Italian regions. Isolates from bovine were most commonly identified as P. zopfii genotype 2, and only in one case as P. blaschkeae, whereas isolates from buffaloes belonged both to P. zopfii genotype 2 and P. wickerhamii . These findings proved the suitability of our multiplex PCRs as a rapid test to discriminate among pathogenic Prototheca strains. Significance and Impact of the Study: This work reports PCR assays based on novel Prototheca spp. mitochondrial and chloroplastic target sequences. The multiplex PCR protocol described in this study is useful for rapid simultaneous detection of P. zopfii, P. wickerhamii and P. blaschkeae .